Adult learning on the edge of a precipice: an ecology of living and learning - Bainbridge, Alan (Adult Education Discourses, 2022)
This article considers adult learning from a ‘long-life’ perspective. Stepping out of contemporary frames that position adult learning as ‘life-long’ or even ‘life-wide’ enables a discussion of adult learning as an evolutionary informed, ecologically meaningful activity. In taking this approach, the paper shows how adult learning has evolved and been maintained by trouble, indeed how the human condition is under continual existential threat. The paper will draw on writings that discuss the evolutionary origins of adult learning, particularly the paradox that humans are both part of, and separate from, the ‘more-than-human’ world (Abram, 1997). The focus of this paper will be on the experience, conscious or unconscious, of living under the continual threat of annihilation and how this may have provided the motive for adult learning behaviours in both our hominid ancestors and contemporary society. The paper begins with a discussion to highlight the nature of human life as one that is always under threat by drawing on religious symbolism, poetry and (in the UK at least) an ever-expanding genre of ‘nature writing’. Having explored what it may feel like to live a life where survival is uncertain, the paper then draws on ecological and evolutionary principles to provide a theoretical ‘long-life’ understanding of adult learning. It is admitted at the outset that the route set out here may appear contradictory, even confusing, but the author asks the reader to first enter into an uncomfortable and troubling world, before the author, finally – despite what might sound like a bleak prospect for humanity – provides resources of hope grounded in the paradoxical potential provided by adult learning.